Noter til studiet af skurkeskabelse som en social praksis - Klapp, Orrin (Slagmark - Tidsskrift for idéhistorie, 2018)
The paper analyzes the ways in which villains are created and villain-images imputed to individuals. Klapp first provides a provisional definition of vilification, which clearly distinguishes between vilification and other forms of malicious social behavior such as scapegoating and libel. He then identifies and describes the different phases of the vilifying process and provides analytical tools for further study of this process. The paper concludes with a brief discussion of whether vilification is an unavoidable social phenomenon.